Caminate axe and Chiaruccia di Fano (PU) settlement between Middle Bronze Age 3 and Recent Bronze Age 1. Matched review in relation to interactions between north-eastern Italy and the peninsula - Gaia Pignocchi; Elisa Dalla Longa; Giovanni Tasca (IpoTESI di Preistoria)
The contribution presents a middle-short wings bronze axe, sporadically found near Caminate di Fano. This artefact is typologically related to the productions from terramare area and north-eastern Italy and it is chronologically ascribable between the end Middle Bronze Age and the beginning of Recent Bronze Age (Peschiera cultural horizon). The artefact is known without any data on the finding (accidental), the place (only partially reconstructable), the archaeological context and the functional interpretation (a deposition? an abandonment?). For this reason, to give a better chronological and cultural framework for the finding, a typological study has been performed. Moreover, an overview of the Middle and Recent Bronze Age settlement of the territory around Fano is given. The study of Caminate axe has indeed offered the occasion to consider its possible relation with the neighbouring settlement of Chiaruccia di Fano. The pottery production of this site, in particular the handles (“a maniglia” handles with expanded horned appendixes, superelevated “a manubrio” handles with vertical expansion and rostrum handles), show clear markers of interactions with north-eastern Italy, from Emilia Romagna to Veneto and Friuli: the same territory where also the references proposed for the axe (within Peschiera production horizon) point. A detailed analysis of the potsherd with “Appenninico” decoration and of handles has been carried out. The references have been drawn both with Marche region area and north-eastern territory, with the aim of finding significant connections between Chiaruccia settlement (northern portion of Marche region) and coeval sites of Emilia Romagna, Veneto and Friuli. Chiaruccia settlement, with its “northern” cultural aspects, even if collocated within Appenninico and Subappenninico cultural aspects, an be read as a “border site” due to its connections with northern area: the same that the axe from Caminate (with a possible interpretation as a votive or a war-related finding) shows.